Tafsir Al-Qur’an di Youtube - Hairul, Moh. Azwar (Jurnal Al-Fanar, 2019)
This article aims to analyze the content of the interpretation of the Qur?an by Nouman Khan which takes YouTube as his media. As the bachelor of Technology, he truly realizes that YouTube is very benefit in delivering his interpretation of Qur?an. There are two main points of this article; first, examining the method of his interpretation as his characteristic. Second: the Effectiveness of his interpretation which is delivered in YouTube as the media. The results of this study indicate that the interpretation conveyed by Nouman Ali Khan through YouTube has characteristics that focus on the linguistic approach that is presented in the form of thematic method and has nuance of sociality aspect. While the results of the interpretation provide three dimensions of effect: first, providing knowledge from the meaning verses of the Qur?an (cognitive effects). Second, Nouman?s interpretation influences the audience?s emotional (affective effect), and third, gives a paradigm and attitude change to the verses of the Qur?an that has been interpreted (behavioral effects)